Observation of the decay Bc±→J/ψπ± and measurement of the Bc± mass - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Álvarez González, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Aoki, M; Apollinari, G; et al. (2008)
The Bc± meson is observed through the decay Bc±→J/ ψπ±, in data corresponding to an integrated luminosity of 2.4fb-1 recorded by the Collider Detector at Fermilab II detector at the Fermilab Tevatron. A signal of 108±15 candidates is observed, with a significance that exceeds 8σ. The mass of the Bc± meson is measured to be 6275.6±2.9(stat)±2.5(syst)MeV/c2. © 2008 The American Physical Society.